Note on the Instruction of April 28, 2025, of the General Directorate of Legal Security and Public Faith, on updating the registration regime for the parentage of births through surrogacy: between the anodyne and the harmful - Durán Ayago, Antonia (CUADERNOS DE DERECHO TRANSNACIONAL, 2025)
We are faced with an Instruction that is clearly detrimental to the interests of children born abroad through surrogacy to Spanish parents. Instead of proposing solutions to these cases, it has effectively short-circuited these children’s access to the Spanish Civil Registry, forcing them to undergo a double determination of parentage in accordance with Spanish regulations, the only ones granted legitimacy. This is a legal absurdity that ignores our system of Private International Law and therefore violates our legal system. It should be repealed as soon as possible.
Keywords: Surrogacy; recognition; best interests of the child